Bis(thiocyanato-κN)[tris(2-pyridylmethyl)amine-κ4N,N′,N′′,N′′′]nickel(II) methanol hemisolvate - Sajini R. Randeniya; Richard E. Norman (Acta Crystallographica Section E, 2009)
The title complex, [Ni(NCS)2(C18H18N4)]·0.5CH3OH, consists of two crystallographically distinct complexes and a methanol solvent molecule. The NiII complexes are pseudo-octahedral six-coordinate, with the tris(2-pyridylmethyl)amine (TPA) ligand providing four N atoms and two N-bound thiocyanates providing the final two N atoms. The distances and angles are typical for NiII–TPA complexes. The compound has unit-cell parameters that are surprisingly similar to the previously reported hydrate.